Model Event Planning dalam Penyelenggaraan Training Masa Persiapan Pensiun oleh PT Arga Nusa Persada - Rana Mustika Silmi; Etty Kongrat (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
Following an event planning model will guide an event organizers to make a successful event. An-event planning used as a systematic framework consisted of several stages of planning an event. This research conduct in PT Arga Nusa Persada, as an event organizer for pre-retirement training. The purpose of this study was to determine the event planning model of the training organizers as one of the market leader for pre-retirement training vendor in Indonesia. The data used by the authors in this study is a qualitative data. Data was collected by observation and structured interview, these data were then written on descriptive way. The research resulting event planning model that used by the organizer is helpful to create a successful event, the step-by-step event planning model can be explained as follows : Decision, Detailed Planning, Implementation and Evaluation.